The Influence of Organizational Culture on PT Performance. Trijaya Alfaria - Ngoc, Huy Dinh Tran (Yayasan Pendidikan Belajar Berdikari, 2023)
The researcher chose PT. Sumber Alfaria Trijaya Bandung Branch as the subject of this review. Because human resources are one of the most crucial components of any organization and cannot be replaced. The researchers aimed to see if work happiness, as an intervening variable, could affect employee performance via organizational culture and career development in this study. This type of research is quantitative in nature. In the process of gathering data, primary and secondary data are employed, and the slovin formula is used to choose samples using probability sampling. The sample size should then be limited to 138 people. Microsoft Office Excel 2019 and Lisrel Software version 8.80 are used in the data analysis procedure. The results show that Organizational Culture has an impact on employee performance, Career Development has an impact on employee performance, and Job Satisfaction affects Employee Performance, Organizational Culture does not affect Employee Performance mediated by Job Satisfaction, Career Development influences Employee Performance mediated by Job Satisfaction.